(untitled) (Revista de Estudos da Linguagem, 2005)
This paper describes the results of a lexical decision task whichwas applied to groups of children in 1st – 4th grades. The mainobjective was to obtain preliminary measurements on which tobase the development of a final version of the same type of task,to be included in the computerized evaluation tool AVACLE (cognitive assessment of reading and writing abilities), already inthe final stage of development by Pinheiro and collaborators. 68children were presented individually with a mixed list of wordsand non-words and instructed to press the Yes-key for words andthe No-key for non-words. Decision reaction time (DRT) and errorpercentage were recorded. As expected, words were recognisedmore rapidly than non-words for all grades. In terms of error, thislexical effect was only significant for 3rd graders. The frequencyeffect was significant for both DRT and accuracy only for 2nd gradersand on DRT for 1st and 3rd graders. The results show how theorthographic lexicon develops, and are discussed according to theinformation processing approach. The test proved to be efficientand, with minimal modifications, will be used as part of the finalversion of the AVACLE evaluation tool.